Molecular dynamics simulations of cancer cell membrane electroporation under the plasma electric field effect. Issue 2 (6th November 2022) - Wang, Huichao; Zhao, Tong; Wang, Zichen; Wang, Xiaolong; Wang, Daohan; Zhang, Yuantao
Abstract: In the cold atmospheric plasma (CAP)‐assisted cancer treatment, the electroporation of cancer cell membranes occurs under the CAP itself electric field effect, leading to changes in membrane permeability. In this paper, using classical molecular dynamics simulations, the electroporation of pure or different cholesterol‐containing phospholipid bilayer models under different pulsed electric fields was studied. The results showed that the electroporation time under a nanosecond pulsed electric field was shorter, while a picosecond pulsed electric field had a stronger penetration effect. Increasing the electric field intensity or decreasing the frequency of cholesterol contents decreased the electroporation time. Our simulation complements the related studies on electroporation under a picosecond pulsed electric field and reveals the potential mechanism of CAP‐selective cancer cell apoptosis. Abstract : The electroporation of pure or different cholesterol‐containing phospholipid bilayer models under different pulsed electric fields. The formation of hydrophilic channels was a necessary condition for electroporation. Increasing the electric field intensity or decreasing the frequency decreased the electroporation time. The cancer cell membranes with low cholesterol contents were more likely to form pores.